Halotolerant Plant Growth-Promoting Bacteria Colonization of Agronomic Crops Under Saline Stress - Sulastri, Sulastri; Wiyono, Suryo; Sopandie, Didy; Santosa, Dwi Andreas (KnE Life Sciences, 2022)
The ability of a plant growth-promoting bacteria (PGPB) strain to colonize the roots and tissues of inoculated plants is important for their successful use in agricultural practices. The purpose of this study was to determine how effective 15 indigenous halotolerant PGPB were at colonizing three different agronomic crops via seed inoculation. Using standard Hoagland’s media and Hoagland’s media amended with 100 mM NaCl, we tested 15 gfp-tagged halotolerant bacterial isolates for their ability to colonize rice, maize, and soybean seedlings. The quantitative dilution plating method and fluorescent microscopy were used to determine the colonization degree of gfp-tagged halotolerant PGPB isolates in the rhizoplane zone and in the inner tissue of the seedlings at 21 days after germination. All halotolerant PGPB isolates colonized the rhizoplane zone of all seedlings. In both standard and 100 mM NaCl amended Hoagland’s media, isolates E194-3, D183-4, and E101-1 showed the highest colonization in rice, maize, and soybean seedlings, respectively. The ability of halotolerant PGPB isolates to colonize agronomic crops was found to vary depending on bacterial isolates, plant species, plant tissues, and NaCl concentration. Keywords: inoculation, colonization, halotolerant, endophyte, rhizoplane